2007
DOI: 10.1182/blood-2006-12-027698
|View full text |Cite
|
Sign up to set email alerts
|

The growing complexity of platelet aggregation

Abstract: Platelet aggregation, the process by which platelets adhere to each other at sites of vascular injury, has long been recognized as critical for hemostatic plug formation and thrombosis. Until relatively recently, platelet aggregation was considered a straightforward process involving the noncovalent bridging of integrin ␣ IIb ␤ 3 receptors on the platelet surface by the dimeric adhesive protein fibrinogen. However, with recent technical advances enabling real-time analysis of platelet aggregation in vivo, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
533
4
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(557 citation statements)
references
References 93 publications
7
533
4
13
Order By: Relevance
“…For comparison purposes, we also study Y polymers, which correspond to u ¼ 0.41 k B T 19,20 . The monomers interact with the colloids at discrete binding sites on the colloid surfaces that mimic the actual GPIb-a receptor on the surface of platelets that specifically binds to the A1 domain of vWF [10][11][12] . The binding process is modelled through the classical model of Bell 21 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison purposes, we also study Y polymers, which correspond to u ¼ 0.41 k B T 19,20 . The monomers interact with the colloids at discrete binding sites on the colloid surfaces that mimic the actual GPIb-a receptor on the surface of platelets that specifically binds to the A1 domain of vWF [10][11][12] . The binding process is modelled through the classical model of Bell 21 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are some instances in nature, however, in which forming a composite very rapidly is necessary, and such conditions are met during blood clotting. During this process, our body forms a polymer-platelet composite called the plug within seconds of injury 10,11 . This aggregate composed of von Willebrand factor (vWF), which is a long biopolymer, and platelets forms the scaffold for the formation of a clot at the site of the lesion.…”
mentioning
confidence: 99%
“…In this assay, human melanoma A375 cells and mouse melanoma B16F10 cells both stably expressing GFP (A375-GFP cells and B16F10-GFP cells) were used. It has been reported that mouse platelets could interact with tumor cells in a P-selectin dependent manner [25][26][27][28][29] and B16F10 cells do not express P-selectin ligand. 12 In order to observe the tumor cell-platelet interactions in lung vessels, platelets were labeled with PKH26 (red), which can not activate platelets and can guarantee the molecules on the platelet surface in its native conformation.…”
Section: The Tumor Cell-platelet Interactions and Lung Metastasis Canmentioning
confidence: 99%
“…Biochemical and hemodynamic factors contribute to thrombus formation at a vulnerable vessel wall (2)(3)(4). Thrombogenic components exposed upon plaque rupture-e.g.…”
mentioning
confidence: 99%